ANTHROPOCENTRIC THEOLOGY IN A BIOPIC FILM : A STUDY OF THE ISLAMIC CONCEPTION OF K.H. HASYIM ASY'ARI IN THE FILM SANG KIAI - Kartika, Bambang Aris (Capture : Jurnal Seni Media Rekam, 2022)
The film Sang Kiai was created based on the biographical history of a person who played a significant role in the Battle of Surabaya on November 10, 1945, a pivotal event in Indonesian history. This film chronicles the story of K.H. Hasyim Asy'ari, a great scholar from Tebuireng Islamic Boarding School in Jombang, the founder and leader of Nahdlatul Ulama (NU), the largest Islamic religious mass organization in Indonesia, as well as a national hero. Accordingly, this study proposes a research problem of the extent to which anthropocentrism theology serves as the foundation for the Islamic conception of K.H. Hasyim Asyari in the movie Sang Kiai. The study of the film Sang Kiai applied an anthropocentric theological reading approach and a qualitative descriptive methodology. The study’s findings reveal that K.H. Hasyim Asy'ari utilized anthropocentric theology to raise Muslims’ awareness to fight the practices of colonialism and break free from its shackles while also fighting the ignorance of aqidah. In sum, anthropocentric theology is the basis for the legitimacy and principles of the Islamic conception of K.H. Hasyim Asy'ari’s attitudes, behavior, thought patterns, and actions to overcome Muslims’ problems.